Assessing nature-positive practices: An application of the economics of ecosystems and biodiversity (TEEB) for agriculture and food evaluation framework - Lichtenthal, Peter; Zhang, Wei; Hettiarachchi, Upeksha (CGIAR System Organization, 2025)
To inform policy and investment that aim to promote nature-positive practices, it is critical to go beyond single metrics such as yield and profitability and comprehensively understand the social, economic, and environmental impact of practices. In this study, using the TEEB for Agriculture and Food (TEBAgriFood) Evaluation Framework (TEEB 2018) to assess four agricultural practices with high potential to contribute positively to biodiversity outcomes is a starting point for identifying the documented main costs and benefits, both visible and “hidden”, of the sustainable management approaches, and their impacts and dependencies on the various types of capitals including biodiversity. The results illuminate the potential co-benefits and tradeoffs in multi-dimensional outcomes that matter to society and shed light on gaps in data and information.